The Role of E-Wom and Pricing in Purchasing Decisions - Amrina, Hafidza Nash’ul; Marsuhin (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2024)
This research aims to delve into the phenomenon of Electronic Word of Mouth (eWOM) in two regions with the highest digital platform users, namely Bojonegoro Regency and Lumajang Regency. The digital era is increasingly shaping a group consistently exposed to online information and interactions, while internet infrastructure in both regions is developing. The impact of eWOM on students' perceptions, preferences, and behaviors, especially in terms of selecting educational institutions, and social interactions within the campus environment. The findings of this study provide insights for educational institutions and students to optimize the benefits and manage risks related to the eWOM phenomenon in specific local contexts. A sample of 284 individuals was selected using probability sampling techniques, and data collection was done using validated and reliable questionnaires. Data analysis techniques employed include partial analysis and multiple regressions. From the analysis results, it is concluded that Electronic Word of Mouth significantly influences purchasing decisions, with pricing also playing a crucial role in product purchasing decisions. Competitive pricing indicators emerge as the most influential in purchasing decisions. The higher the level of eWOM, the higher the decision to visit consumers, and vice versa. This conclusion implies that creating positive eWOM can increase the number of purchases for companies, and price management influences purchasing decisions, especially in the context of online shopping platforms such as Shopee.